2022
DOI: 10.3390/nu14020352
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome and Organ Fibrosis

Abstract: Fibrosis is a pathological process associated with most chronic inflammatory diseases. It is defined by an excessive deposition of extracellular matrix proteins and can affect nearly every tissue and organ system in the body. Fibroproliferative diseases, such as intestinal fibrosis, liver cirrhosis, progressive kidney disease and cardiovascular disease, often lead to severe organ damage and are a leading cause of morbidity and mortality worldwide, for which there are currently no effective therapies available.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 259 publications
0
16
0
4
Order By: Relevance
“…A lot of evidence has demonstrated that the imbalance of intestinal flora promotes CF progression [ 42 , 43 ]. Herein, QHF treatment regulated the gut microbiota structure.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of evidence has demonstrated that the imbalance of intestinal flora promotes CF progression [ 42 , 43 ]. Herein, QHF treatment regulated the gut microbiota structure.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, low circulating LPS levels provoke cardiac fibrosis, even without any prior myocardial injury [ 62 ]. Since toll-like receptor-4 (TLR-4) is expressed in cardiac fibroblasts, for which LPS is a ligand, these cells directly respond to LPS by activating the NLRP3 inflammasome, further contributing to inflammation and fibrosis [ 3 ]. A recent prospective observational study has shown a strong association between circulating LPS and major adverse cardiovascular events (MACE) in a large cohort of AF patients [ 63 ].…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…In this regard, gut microbiota dysbiosis, high exposure to endotoxin, and an increased trimethylamine N-oxide (TMAO) level represent novel possible risk factors for CVDs along with abnormal sleep duration, genetic markers, air pollution and environmental noise. The major advances in high-throughput sequencing technology and metabolomics have explored the pivotal role of GMB and its metabolites in regulating both inflammatory and fibrotic responses and further cardiac remodeling in a host organism [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of the initial etiology, tubular cell atrophy and interstitial fibrosis are cardinal pathological features of CKD. Renal fibrosis has a typical feature of excessive accumulation and deposition of extracellular matrix components [18]. In terms of underlying molecular mechanism, renal fibrosis is associated with the activated pathways, such as transforming growth factor-β/Smad, Wnt/β-catenin, inhibitory of kappa B (IκB)/nuclear factor kappa B (NF-κB), and Keap1/nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathways [19][20][21][22][23], as well as the activated cytokines, such as renin-angiotensin system and aryl hydrocarbon receptor [24][25][26][27] and the dysregulation of metabolites such as amino acids and lipids [28][29][30].…”
Section: Introductionmentioning
confidence: 99%